MECHANIZED AND ROTARY SYSTEMS IN ROOT CANAL PREPARATION (International Seven Journal of Multidisciplinary, 2026)
The biomechanical preparation of the root canal system is a fundamental step for the success of endodontic treatment, as it is directly related to the removal of microorganisms, organic tissues, and dentinal debris. With technological advances, mechanized and rotary nickel-titanium (NiTi) systems have assumed a central role in clinical practice, providing greater efficiency, predictability, and safety when compared to traditional manual instrumentation. The present study aims to review recent scientific literature on mechanized and rotary systems used in root canal preparation, discussing their characteristics, advantages, limitations, and association with irrigation protocols. This is a narrative bibliographic review conducted using the PubMed database, with the selection of articles published over the last five years. The analyzed studies demonstrate that mechanized systems promote better centering of canal preparation, reduction of procedural errors, and optimization of clinical time, especially in curved canals and those with complex anatomy. However, evidence indicates that no instrumentation technique is capable of reaching all root canal surfaces, making the association with chemical irrigants and activation methods indispensable. It is concluded that mechanized and rotary systems represent a significant advance in contemporary endodontics, provided they are used judiciously and integrated into effective irrigation protocols.